Effects of cleavage by a disintegrin and metalloproteinase with thrombospondin motifs-4 on gene expression and protein content of versican and aggrecan in the digital laminae of horses with starch gruel–induced laminitis - Wang, Le (2012)
OBJECTIVE: To determine whether increased gene expression of a disintegrin and metalloproteinase with thrombospondin motifs-4 (ADAMTS-4) in laminae of horses with starch gruel– induced laminitis is accompanied by increased enzyme activity and substrate degradation. SAMPLE: Laminae from the forelimb hooves of 8 healthy horses and 17 horses with starch gruel–induced laminitis (6 at onset of fever, 6 at onset of Obel grade 1 lameness, and 5 at onset of Obel grade 3 lameness). PROCEDURES: Gene expression was determined by use of cDNA and real-time quantitative PCR assay. Protein expression and processing were determined via SDS-PAGE and quantitative western blotting. Protein distribution and abundance were determined via quantitative immunofluorescent staining. RESULTS: ADAMTS-4 gene expression was increased and that of versican decreased in laminitic laminae, compared with expression in healthy laminae. Catalytically active ADAMTS-4 also was increased in the tissue, as were ADAMTS-4–cleavage fragments of versican. Immunofluorescent analyses indicated that versican was depleted from the basal epithelia of laminae of horses at onset of Obel grade 3 lameness, compared with that in healthy laminae, and this was accompanied by regional separation of basal epithelial cells from the basement membrane. Aggrecan gene and protein expression were not significantly affected. CONCLUSIONS AND CLINICAL RELEVANCE: Changes in gene and protein expression of ADAMTS-4 and versican in the basal epithelium of laminitic laminae indicated a fundamental change in the physiology of basal epithelial cells. This was accompanied by and may have caused detachment of these cells from the basement membrane.